Preferential treatment of government bonds in liquidity regulation: Implications for bank behaviour and financial stability - Ulrike Neyer; André Sterzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
This paper analyses the impact of different treatments of government bonds in bank liquidity regulation on financial stability. Using a theoretical model, we show that a sudden increase in sovereign default risk may lead to liquidity issues in the banking sector, implying the insolvency of a significant number of banks. Liquidity requirements do not contribute to a more resilient banking sector in the case of sovereign distress. However, the central bank acting as a lender of last resort can prevent illiquid banks from going bankrupt. Then, introducing liquidity requirements in general and repealing the preferential treatment of government bonds in liquidity regulation in particular actually undermines financial stability. The driving force is a regulation-induced change in bank investment behaviour.
Keywords: G28; G21; G01; 330; bank liquidity regulation; government bonds; sovereign risk; financial contagion; lender of last resort